Optical Constants of α- and β-Zinc(II)-Phthalocyanine Films. (20th December 2012) - Kozlik, Michael; Paulke, Sören; Gruenewald, Marco; Forker, Roman; Fritz, Torsten
Abstract : We present a dataset of the optical constants of α - and β -zinc(II)-phthalocyanine (ZnPc). They were determined accurately from transmission and differential reflectance spectra, with the surface roughness taken into account. For this purpose, thin films were prepared on quartz glass substrates via physical vapor deposition and characterized by ultraviolet-visible (UV-Vis) spectroscopy before as well as after a well-defined annealing process. Kramers-Kronig consistency of the optical constants obtained was checked by means of a numerical algorithm.